Cell age–specific vulnerability of neurons to anesthetic toxicity. Issue 6 (5th June 2013) - Hofacer, Rylon D.; Deng, Meng; Ward, Christopher G.; Joseph, Bernadin; Hughes, Elizabeth A.; Jiang, Connie; Danzer, Steve C.; Loepke, Andreas W.
<x xml:space="preserve">Abstract</x> Objective Anesthetics have been linked to widespread neuronal cell death in neonatal animals. Epidemiological human studies have associated early childhood anesthesia with long‐term neurobehavioral abnormalities, raising substantial concerns that anesthetics may cause similar cell death in young children. However, key aspects of the phenomenon remain unclear, such as why certain neurons die, whereas immediately adjacent neurons are seemingly unaffected, and why the immature brain is exquisitely vulnerable, whereas the mature brain seems resistant. Elucidating these questions is critical for assessing the phenomenon's applicability to humans, defining the susceptible age, predicting vulnerable neuronal populations, and devising mitigating strategies. Methods This study examines the effects of anesthetic exposure on late‐ and adult‐generated neurons in newborn, juvenile, and adult mice, and characterizes vulnerable cells using birth‐dating and immunohistochemical techniques. Results We identify a critical period of cellular developmental during which neurons are susceptible to anesthesia‐induced apoptosis. Importantly, we demonstrate that anesthetic neurotoxicity can extend into adulthood in brain regions with ongoing neurogenesis, such as dentate gyrus and olfactory bulb. Interpretation Our findings suggest that anesthetic vulnerability reflects the age of the neuron, not the age of the organism, and therefore may potentially not only be relevant to children but also to adults undergoing anesthesia. This observation further predicts differential heightened regional vulnerability to anesthetic neuroapoptosis to closely follow the distinct regional peaks in neurogenesis. This knowledge may help guide neurocognitive testing of specific neurological domains in humans following exposure to anesthesia, dependent on the individual's age during exposure. ANN NEUROL 2013;73:695–704